Heavy Metals Concentration in Muscle Tissue of Threatened Sharks (Rhizoprionodon acutus, Sphyrna lewini, and Squallus hemipinnis) from Binuangeun, Lebak Banten, Indonesia - Suratno Suratno; Dwi Siswanta; Satriyo Krido Wahono; Nurul Hidayat Aprilita (Indonesian Journal of Chemistry, 2022)
Metals accumulation in threatened sharks’ meat represents a global health issue. The objective of the current study was to measure the concentration of six metals (Li, Ti, Ni, Cd, As, and Pb) using ICP-MS in threatened sharks’ meat of Rhizoprionodon acutus, Squalus hemipinnis, and Sphyrna lewini from Binuangeun Fish Auction in Lebak, Banten, Indonesia. The results showed that the concentration of Ni, Li, Cd, and Pb was below the acceptable levels for food sources for human consumption, except for As concentration (more than 30 fold higher). This study showed high levels of Ti concentration in all threatened sharks' meat. Overall, this study shows that an accumulation of Ti in sharks' meat should be considered a risk to the health of seafood consumers.